The insight and the risk of psychiatric re-hospitalization in patients suffering from schizophrenia - Pawełczak, Paweł; Karakuła, Hanna; Wróbel, Aleksandra; Stecka, Mariola (Current Problems of Psychiatry, 2012)
Despite significant advances in the treatment and rehabilitation of schizophrenic patients, high relapse rates in the course of this disease are still observed, frequently resulting in psychiatric hospitalization. Insight into illness is an important component of the presentation and its level may play an important role in assessing risk of hospitalization in the course of schizophrenia.This paper reviews the literature in order to determine relationships between insight into illness and the risk of hospital readmission among schizophrenic patients. Due to the complexity of the phenomenon of insight, study findings in this area are not always consistent. Lower insight may be associated with poorer compliance, more fulminant course of illness and more frequent occurrence of aggressive behavior in patients with schizophrenia, which consequently may predispose to more frequent psychiatric hospitalizations.On the other hand, lower insight may also contribute to lower severity of depressive symptoms and suicidal tendencies, which in turn may reduce the risk of hospitalization. The studies on relationships between the level of insight into illness in schizophrenia and the risk of hospitalization have to date yielded no conclusive results and should be continued.